2008
DOI: 10.1007/s00464-008-9932-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood vessel sealing among new electrosurgical and ultrasonic devices

Abstract: Among the new 5-mm laparoscopic electrosurgical and ultrasonic instruments available for testing, RX, LS, and FT produced the highest mean burst pressures. FT had the shortest mean seal times for medium and large vessels. Minimal or no seal failures occurred with HS, RX, LS, LM, and FT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 17 publications
10
111
1
7
Order By: Relevance
“…Both technologically advanced, they have been suggested to have excellent results and minimal lateral thermal injury. [1][2][3][4][5][6]10,12,13 The Harmonic scalpel controls bleeding by tamponating the vessel and sealing it with a protein coagulum at temperatures ranging from 50°C to 100°C. The Harmonic scalpel works at lower temperatures than electrosurgical devices, since it denatures proteins by mechanically breaking the hydrogen bounds in protein molecules when the blade vibrates at 55.5 kHz, thus generating much less heat from tissue friction.…”
Section: Discussionmentioning
confidence: 99%
“…Both technologically advanced, they have been suggested to have excellent results and minimal lateral thermal injury. [1][2][3][4][5][6]10,12,13 The Harmonic scalpel controls bleeding by tamponating the vessel and sealing it with a protein coagulum at temperatures ranging from 50°C to 100°C. The Harmonic scalpel works at lower temperatures than electrosurgical devices, since it denatures proteins by mechanically breaking the hydrogen bounds in protein molecules when the blade vibrates at 55.5 kHz, thus generating much less heat from tissue friction.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid development in minimally invasive techniques has driven the need for concomitant advances in instrumentation. Currently, available instruments with tissue-sensing technology can seal blood vessels with supraphysiological burst pressures equal to those obtained with surgical clips or ligatures (19,20). PTG is one of the new electrosurgical devices that can provide vessel sealing.…”
Section: Discussionmentioning
confidence: 99%
“…At the highest power setting, we found slightly less thermal injury caused by the Harmonic scalpel (127.48 lm) than LigaSure (144.18 lm), but that difference was nonsignificant. Certain studies, e.g., Diamantis et al; Sutton et al [26,28] in their studies, found that LigaSure (197.79 lm) might cause less thermal injury than Harmonic scalpel (205.61 lm) but that difference was not significant. Sartori and colleagues [18] found that the only real advantage between LigaSure and Harmonic scalpel was a shorter duration of surgery with the Harmonic scalpel, probably owing to its ability to coagulate and cut at the same time.…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 94%
“…Minimizing thermal damage to surrounding tissues without compromising safety and tissue integrity is of importance in surgery. Ultrasonic instruments are tried to be safer than traditional diathermy [7,20,[24][25][26]. The Ultrasonic shears incorporate piezoelectric transducers that induce a vibration frequency at the functional tip and transduces a lower amount of energy to the tissue than high-frequency current or laser techniques, resulting in reduced lateral thermal damage and penetration depth owing to lower temperatures [7,20,27].…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 99%
See 1 more Smart Citation